Il cinema italiano del secondo dopoguerra e la controversa questione della discontinuità: nuove strade, antichi territori? - Francesco Pitassio (Storicamente)
The article focuses on the Italian cinema in building collective memory in post-war transitional phase. It tackles neorealist humanism and descriptive style, together with its obliteration of Fascism. These features contribute to ‘cultural trauma’: a symbolic activity reshaping collective identity. Finally, the article scrutinizes non-fiction works representing a contested area, in political and historical terms: Trieste. This final pace sheds light on the degree of diffusion of cultural trauma and clarifies how the concealment of Fascism operated as parapraxis.